Brucella abortus and Brucella melitensis infections in humans: a case series highlighting diagnostic and epidemiological profile - Kumari, Renu; Kalyan, Raj Kumar; Ramakrishna, Vangala; Jain, Amita; Kumar, Puneet; Gupta, Kamlesh Kumar; Verma, Sanjeev Kumar (International Journal of Research in Medical Sciences, 2025)
Brucellosis is a major zoonotic infection caused by Brucella species, commonly acquired through contact with infected animals or ingestion of unpasteurized dairy products. Its varied clinical manifestations and nonspecific symptoms often delay diagnosis, complicating patient management. This case series describes the clinical, diagnostic, and epidemiological features of eight confirmed brucellosis cases from a tertiary care centre. Diagnosis was established using rose Bengal plate test (RBPT), serum agglutination test (SAT), enzyme-linked immunosorbent assay (ELISA) IgM antibody detection, and real-time PCR. Species identification was performed through conventional PCR targeting the IS711 gene, followed by Sanger sequencing. Clinical data, laboratory findings, risk factors, co-infections, and treatment outcomes were systematically documented. Of the eight cases, five were infected with B. abortus and three with B. melitensis. Joint pain was universal, with sacroiliitis in two patients and rheumatoid arthritis in another two. Most patients had normal haematological parameters, with mildly elevated inflammatory markers (CRP, ESR). Rural exposure, livestock contact, and consumption of animal products were the predominant risk factors in B. abortus cases. In contrast, B. melitensis cases occurred in urban residents with no direct animal exposure, suggesting foodborne transmission. Three patients presented with co-infections (Leptospira, dengue, malaria and salmonella), while two patients with underlying malignancies succumbed. All were treated with doxycycline and rifampicin for six weeks, as per WHO guidelines. This series emphasizes the persistence of brucellosis in rural India and the emergence of B. melitensis in urban settings. Early diagnosis, molecular species identification, and integrated one health interventions are critical to reducing disease burden.